PRACTICES AND ETHICS: IN THEOLOGICAL AND SOCIOLOGICAL PERSPECTIVE - Agustin, Marliana (Spektra: Jurnal Ilmu-ilmu Sosial, 2021)
Morals and ethics have a role in shaping civil society, in which civil society is the ideal society for today. But the problem is that sometimes in society they tend not to understand morals and ethics theologically or sociologically. Morals and ethics in a sociological perspective have the same meaning. The only difference is theologically, if the basic morals are Al-Quran and Al-Hadith. While ethics and morals are relative, dynamic, and relative because they are human understanding and meaning through the elaboration of their ijtihad on good and bad issues for the welfare of human life in the world and the happiness of life in the hereafter.